Fine-resolution mapping of spontaneous and double-strand break-induced gene conversion tracts in Saccharomyces cerevisiae reveals reversible mitotic conversion polarity. - Sweetser, D B (1994)
Spontaneous and double-strand break (DSB)-induced gene conversion was examined in alleles of the Saccharomyces cerevisiae ura3 gene containing nine phenotypically silent markers and an HO nuclease recognition site. Conversions of these alleles, carried on ARS1/CEN4 plasmids, involved interactions with heteroalleles on chromosome V and were stimulated by DSBs created at HO sites. Crossovers that integrate plasmids into chromosomes were not detected since the resultant dicentric chromosomes would be lethal. Converted alleles in shuttle plasmids were easily transferred to Escherichia coli and analyzed for marker conversion, facilitating the characterization of more than 400 independent products from five crosses. This analysis revealed several new features of gene conversions. The average length of DSB-induced conversion tracts was 200 to 300 bp, although about 20% were very short (less than 53 bp). About 20% of spontaneous tracts also were also less than 53 bp, but spontaneous tracts were on average about 40% longer than DSB-induced tracts. Most tracts were continuous, but 3% had discontinuous conversion patterns, indicating that extensive heteroduplex DNA is formed during at least this fraction of events. Mismatches in heteroduplex DNA were repaired in both directions, and repair tracts as short as 44 bp were observed. Surprisingly, most DSB-induced gene conversion tracts were unidirectional and exhibited a reversible polarity that depended on the locations of DSBs and frameshift mutations in recipient and donor alleles.